Megakaryocytic alterations in bone marrow aspiration smears in thrombocytopenia (Journal of Pathology of Nepal, 2019)
Background: Thrombocytopenia can be seen in any patients irrespective of age and the causes are diverse. This study was done to determine the frequency of various conditions associated with thrombocytopenia and to assess the number and morphology of megakaryocytes in various cases of thrombocytopenia. Megakaryocytic alterations in myelodysplastic versus non-myelodysplastic conditions were also evaluated in this study.Materials and methods: This was a prospective study conducted on 132 cases of bone marrow aspirates of thrombocytopenia over a duration of one year from 14th April 2017 to 13th April 2018 in Tribhuvan University Teaching Hospital, Kathmandu. All the statistical evaluation was done by using SPSS version 24.Results: In this study of 132 cases, megakaryocytic thrombocytopenia was the most common cause of thrombocytopenia for which bone marrow aspiration was done. The most common dysplastic change observed in megakaryocytes was micro megakaryocyte which was more commonly seen in MDS. Nondysplastic changes frequently observed were immature forms followed by bare nuclei and were more frequently seen in megakaryocytic thrombocytopenia followed by in myelodysplastic syndromes.Conclusions: Many similar morphological changes were observed in megakaryocytes among different hematological diseases. So, the presence of dysplastic megakaryocyte should not prompt an interpretation of myelodysplastic syndromes and should always be correlated with patient’s clinical and hematological parameter.